2007
DOI: 10.1007/s11240-007-9220-9
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione metabolism and antioxidant responses during Eleutherococcus senticosus somatic embryo development in a bioreactor

Abstract: Compared to non-embryogenic callus, proembryonic mass, globular, and heart-shaped embryos of Eleutherococcus senticosus had higher levels of endogenous reduced glutathione (GSH). GSH content declined during the course of the embryo development (torpedo and cotyledon). Similarly, glutathione reductase that is involved in the recycling of GSH providing a constant intracellular level of GSH was also higher in globular and heartshaped embryos. The transient increase in GSH contents also correlated with the changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 45 publications
2
12
0
Order By: Relevance
“…APX and GR are the key players involved in AscorbateGlutathione cycle also known as Foyer-Halliwell-Asada cycle. There is less literature available regarding the changes in APX and GR activities during different stages of somatic embryogenesis (Stasolla and Yeung, 2001;Shohael et al, 2007). Similar to our results, increased level of APX was also detected during initial stages in saffron somatic embryogenesis (Blazquez et al, 2009).…”
Section: Antioxidant Enzyme Activitiessupporting
confidence: 89%
See 1 more Smart Citation
“…APX and GR are the key players involved in AscorbateGlutathione cycle also known as Foyer-Halliwell-Asada cycle. There is less literature available regarding the changes in APX and GR activities during different stages of somatic embryogenesis (Stasolla and Yeung, 2001;Shohael et al, 2007). Similar to our results, increased level of APX was also detected during initial stages in saffron somatic embryogenesis (Blazquez et al, 2009).…”
Section: Antioxidant Enzyme Activitiessupporting
confidence: 89%
“…Reduced glutathione (GSH) and its oxidised form (GSSG) work as redox metabolites in most biological system and GR is one of the important enzyme that regulates GSH:GSSG ratio (Mittler et al, 2004). In accordance to our results, Shohael et al (2007) also demonstrated low endogenous levels of GR in non embryogenic callus while the activity was highest in globular and heart stage somatic embryoids. They also reported upregulated level of GSH in globular and heart shaped embryo and this uregulation is brought by the high activity of GR.…”
Section: Antioxidant Enzyme Activitiessupporting
confidence: 87%
“…Antioxidant responses, through alterations of the ascorbate-glutathione redox systems, have been described in several systems, including embryo development (Carimi et al 2003;Belmonte et al 2005). Cell division and embryonic development are supported by GSH availability in a large number of different species together with increased glutathione reductase activity (Shohael et al 2007). These findings are in agreement with the positive correlation between GSH accumulation and the development of PLBs observed in our experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Direct embryogenesis reduces the time required for plant propagation, which may be beneficial to minimize culture-induced genetic changes. Somatic embryogenesis offers an excellent experimental system to study the physiological and biochemical aspects of embryo development (Shohael et al 2007). In addition, somatic embryogenesis is useful for artificial seed production (Maruyama et al 2003), cryopreservation (Yin and Hong 2010;Kong and von Aderkas 2011), genetic manipulations (Capelo et al 2010;Khan et al 2010;Parimalan et al 2010), and large scale propagation (Chen et al 2010;Menéndez-Yuffá et al 2010).…”
Section: Introductionmentioning
confidence: 99%